Stress and emotional intelligence in adults during the pandemic of COVID-19 in Tacna 2020 - Torres Ramos, Luisa Elizabeth (2021)
Stress is a normal reaction in human behavior, and emotional intelligence (EI) plays a fundamental role for its success, both are attributable to psychosocial factors, however, due to the situation that we currently live in our society due to the pandemic COVID-19, the need arises to study both variables, stress and emotional intelligence, with the relationship between both still little explored. The objective of the present study was to identify the relationship between stress and emotional intelligence in adults in the city of Tacna, in a sample of 154 voluntary participants of both sexes. The study design is non-experimental, cross-sectional and correlational. To measure the stress variable, the two-dimensional DASS-21 instrument (anxiety and stress) was used and the TMMS-24 instrument was used to measure the emotional intelligence variable, which includes three dimensions (perception, understanding and regulation). The results obtained indicate that there is a significant correlation between the two dimensions of the stress variable and the perception, understanding and regulation dimensions of the IE variable.